2015
DOI: 10.1021/acs.jpcb.5b05391
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Folic Acid and Poly(amidoamine) Dendrimer Interactions with Folate Binding Protein: A Force-Pulling Study

Abstract: Atomic force microscopy force-pulling experiments have been used to measure the binding forces between folic acid (FA) conjugated poly(amidoamine) (PAMAM) dendrimers and folate binding protein (FBP). The generation 5 (G5) PAMAM conjugates contained an average of 2.7, 4.7, and 7.2 FA per dendrimer. The most probable rupture force was measured to be 83, 201, and 189 pN for G5-FA2.7, G5-FA4.7, and G5-FA7.2, respectively. Folic acid blocking experiments for G5-FA7.2 reduced the frequency of successful binding even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…This in silico experiment is of high relevance since force-pulling has recently been performed with atomic force microscopy for characterizing the interaction of PAMAM dendrimer and folate-binding protein. 70 The SDMD-derived HSA-binding affinities for PAMAM dendrimers of different sizes and surface chemistries were consistent with previous experimental measurements. 45 Our results highlighted the importance of surface modifications with zwitterionic ligands to reduce nonspecific protein binding for the design of stealthy NPs.…”
Section: Introductionsupporting
confidence: 88%
“…This in silico experiment is of high relevance since force-pulling has recently been performed with atomic force microscopy for characterizing the interaction of PAMAM dendrimer and folate-binding protein. 70 The SDMD-derived HSA-binding affinities for PAMAM dendrimers of different sizes and surface chemistries were consistent with previous experimental measurements. 45 Our results highlighted the importance of surface modifications with zwitterionic ligands to reduce nonspecific protein binding for the design of stealthy NPs.…”
Section: Introductionsupporting
confidence: 88%
“…This allows targeting of receptors that are exclusively overexpressed on specific cancer cell surfaces [ 16 ], e.g., the folate receptor (FR) which has been shown to be overexpressed in cancers including ovarian, thyroid, kidney, endometrial, breast and renal cell carcinomas [ 17 ]. These FRs bind avidly to folic acid (FA), a dietary supplement which is intrinsically involved in cellular turnover and accommodates the extreme proliferation of cancer cells [ 18 ]. It was reported that nanocomplexes containing FA enhanced intracellular delivery of anticancer agents [ 19 , 20 ], mRNA [ 15 ] and siRNA [ 12 , 21 , 22 ] in cells overexpressing the FR.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have suggested that the strong binding avidity is also due to a network of van der Waals and electrostatic interactions that form between the FBP and dendrimer. 34,35 The dendrimer-FBP interactions are initiated by a folate-keyed interaction after which a slow-onset tight binding occurs between the dendrimer and receptor. While it seems clear that an optimized ligand conjugation is needed for target cell specificity and initiating cellular interactions, these new findings suggest that other features of the dendritic structure also play a role in governing their cellular interactions and targeting capabilities.…”
Section: Specific Biological Interactions Of Dendrimers Mediated By Surface Ligandsmentioning
confidence: 99%